Mycophenolic acid upregulates miR-142-3P/5P and miR-146a in lupus CD4+T cells. (August 2015) - Tang, Q; Yang, Y; Zhao, M; Liang, G; Wu, H; Liu, Q; Xie, Y; Li, D; Dai, Y; Yung, S; Chan, T M; Lu, Q
Background: Mycophenolic acid (MPA), the active metabolite of mycophenolate mofetil (MMF), is a noncompetitive inhibitor of inosine monophosphate dehydrogenase, and is now widely used for the treatment of systemic lupus erythematosus (SLE). Dysregulated expression of microRNA has been reported to be associated with the pathogenesis of SLE. However, it is unexplored whether altering microRNA expression in SLE patients is one of the therapeutic effects of MPA. Objectives: This study thus aims to investigate the effect of MPA on microRNAs expression in lupus CD4 + T cells and its underlying mechanisms. Results: According to our microarray data, 101 upregulated microRNAs and 77 downregulated microRNAs were identified in MPA-treated lupus CD4 + T cells. Among these microRNAs, miR-142-3p/5p and miR-146a expression was found to be significantly increased in MPA-treated lupus CD4 + T cells compared to untreated controls. Furthermore, we observed that MPA-treated CD4 + T cells from patients with SLE showed enriched levels of H4 acetylation in the putative miRNA-142 regulatory region and enhanced levels of H3 acetylation in the putative miRNA-146a regulatory region compared to untreated cells. Conclusion: Data from this study suggest that MPA activates miR-142 and miR-146a expression through histone modification at the promoter region, which may partially explain the pharmacological mechanisms of MPA for SLE.